Low turn-on field and high field emission current density from Ag/TiO 2 nanocomposite - Patil, Girish P.; Deore, Amol B.; Bagal, Vivekanand S.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Chemical Physics Letters, 2016)
High current density of 1.24 mA/cm2 was drawn at an applied field of 4.4 V/μm from Ag/TiO2 nanocomposite. Also the turn-on field has been reduced from 3.9 V/μm to 2.7 V/μm for the emission current density of 10 μA/cm2. Ag/TiO2 nanocomposite was synthesized by using UV-switchable reducing agent. TiO2 nanotube wall was decorated by Ag nanoparticles with average diameter of 17 nm. To the best of our knowledge this is the first report on the field emission studies of Ag/TiO2 nanocomposite. Simple synthesis route coupled with superior field emission properties indicate the possible use of Ag/TiO2 nanocomposite for micro/nanoelectronic devices.

Observation of enhanced field emission properties of Au/TiO2 nanocomposite - Patil, Girish P.; Bagal, Vivekanand S.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Applied Physics A-Materials Science & Processing, 2016)
Simple and low-cost method of thermal annealing was used to decorate Gold (Au) nanoparticles on aligned TiO2 nanotubes. The aligned TiO2 nanotubes were decorated by Au nanoparticles with an average diameter of 9, 18 and 28 nm (aligned TiO2 nanotubes referred as specimen A and TiO2 nanotubes decorated by Au nanoparticles with average diameter of 9, 18 and 28 nm are referred as specimen B, C and D, respectively). The detailed characterization such as structural, morphological and elemental analysis of TiO2 and Au/TiO2 nanocomposite have been carried out using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, X-ray photoelectron spectroscopy and Raman spectroscopy. Furthermore, the meticulous comparative field emission characteristics of the aligned TiO2 nanotubes and Au/TiO2 nanocomposite have been performed. The turn-on field defined for the current density of 10 mu A/cm(2) has been found to be 3.9, 2.8, 3.2 and 3.7 V/mu m for specimen A, B, C and D, respectively. The observed low turn-on field of specimen B has been found to be superior than the other semiconducting nanocomposites reported in the literature. The emission current stability over a period of 3 h is found to be better for all the specimens. To the best of our knowledge, a systematic field emission study of Au/TiO2 nanocomposite has not been explored. The observed superior field emission study of Au/TiO2 nanocomposite indicates their possible use in micro/nanoelectronic devices.

Surface modification of aligned CdO nanosheets and their enhanced field emission properties - Bagal, Vivekanand S.; Patil, Girish P.; Deore, Amol B.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (RSC Advances, 2016)
Porous aligned CdO nanosheets were grown on a cadmium (Cd) substrate by the simple and cost effective method of thermal annealing. Further, decoration of gold (Au) nanoparticles on the porous aligned CdO nanosheets (specimen A) was achieved by coating with a Au thin film and subsequent annealing treatment. The average diameters of decorated Au nanoparticles were found to be 15 nm, 21 nm and 28 nm for the Au thin films with 20 s, 40 s and 60 s (specimens B, C, and D) coating times. Detailed characterizations, such as structural and morphological analysis of porous CdO nanosheets and Au/CdO nanocomposite (Au decorated porous CdO nanosheets), have been carried out using a Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD) and a Transmission Electron Microscope (TEM). Field emission studies of specimens A, B, C and D were carried out in the planar diode configuration. Turn-on fields of 1.9 V mu m(-1), 1.1 V mu m(-1), 2.4 V mu m(-1) and 2.8 V mu m(-1) have been found for the emission current density of 10 RA cm(-2) for specimens A, B, C and D, respectively. The observed low turn -on field of specimen B (Au diameter of 15 nm) was found to be superior to other semiconducting nanostructures reported in the literature. The field emission current stability over a period of 3 h at the preset current density of 1 RA cm(-2) is found to be excellent for all specimens. To the best of our knowledge, field emission studies along with surface modification of porous aligned CdO nanosheets have not been reported in the literature. The simple synthesis route, facile surface modification and the superior field emission results make the present emitter very suitable for micro/nano electronic devices.